Desain Pembelajaran Kokurikuler Berbasis Pendekatan Pembelajaran Mendalam untuk Pengembangan Dimensi Profil Lulusan Sekolah Katolik: Co-curricular Learning Design Based on deep Learning Approach for Developing Catholic School Graduate Profile Dimensions - Elizabeth Ratih Maharani (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
The study aims to describe how Catholic schools implement co-curricular activities by integrating government policies and the vision of Catholic education to achieve graduate dimensions profiles. The research used a descriptive qualitative method with a case study at SDK Hati Kudus in Samarinda for phase C students. The results showed that co-curricular model was developed based on an analysis of student needs and the integration of the graduate profile dimensions, school’s core values, and the vision of Catholic education. Learning was designed to meet national curriculum standards and to be a means of developing Christian virtues through authentic learning experiences that combine knowledge, faith, and life. The deep learning approach served as a pedagogical foundation that encourages active engagement and reflection among students. The findings also identified character strengthening in accordance with established profile dimensions. The implementation faced challenges related to the teachers' capacity to carry out their professional roles as teachers and as faith educators. Overall, this study confirmed that the co-curricular learning has the potential to be an effective strategy in realizing holistic and transformative education that is in line with national policies and the vision of Catholic education.